Optimism on quality of life in Portuguese chronic patients: moderator/mediator? - Vilhena, E. (2015)
OBJECTIVE: optimism is an important variable that has consistently been shown to affect adjustment to quality of life in chronic diseases. This study aims to clarify if dispositional optimism exerts a moderating or a mediating influence on the personality traits-quality of life association, in Portuguese chronic patients. METHODS: multiple regression models were used to test the moderation and mediation effects of dispositional optimism in quality of life. A sample of 729 patients was recruited in Portugal's main hospitals and completed self-reported questionnaires assessing socio-demographic and clinical variables, personality, dispositional optimism, quality of life (QoL) and subjective well-being (SWB). RESULTS: the results of the regression models showed that dispositional optimism did not moderate the relationships between personality traits and quality of life. After controlling for gender, age, education level and severity of disease perception, the effects of personality traits on QoL and in SWB were mediated by dispositional optimism (partially and completely), except for the links between neuroticism/openness to experience and physical health. CONCLUSION: dispositional optimism is more likely to play a mediating, rather than a moderating role in personality traits-quality of life pathway in Portuguese chronic patients, suggesting that "the expectation that good things will happen" contributes to a better quality of life and subjective well-being.